Comparison of Characteristics and Survival between Prospective and Retrospective Korea Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome Cohort Studies - Kim, Jun Hyoung (Infect Chemother, 2019)
By comparing the data of prospectively and retrospectively enrolled cohorts, we evaluated whether the prospective cohort represented all patients in the retrospective cohort. The prospectively enrolled subjects were older and had lower CD4+ T cell counts, higher viral load. In addition, the initial antiretroviral treatment regimen of the prospective cohort consisted of less integrase strand transfer inhibitor-containing regimens. The 20-year survival rate was 51.8% in the prospective cohort and 84.6% in the retrospective cohort, respectively (P = 0.844). This study suggests the prospective cohort study may not represent all patients.